Food Security, Environments, Nutrition: Structured Evidence (FoodSENSE) Framework application in Mpigi District, Central Uganda - Caulfield, Mark; Omosa, Esther; Hammond, Jim; Achandi, Esther, L.; Ahumuza, Ronnie; Spray, Andrea; Dominguez-Salas, Paula; Ouma, Emily A. (International Livestock Research Institute, 2025)
There is an increasing recognition that achieving food security and good nutrition requires coordinated action between multiple sectors. The causes of food and nutrition insecurity are multifaceted and often interlinked. To improve food security, a good understanding of the different dimensions in the food system and food environment is important to prioritize intervention points. The concept of the ‘food system’ has become an organizing narrative in recent years, with UN agencies and national governments developing food systems action plans aimed at addressing food insecurity and promoting healthy diets for all. There is, however, a gap at finer-grained spatial levels: there are few guidelines on how to implement food systems thinking at the more local levels, to guide local decision-making.